Filsafat Pendidikan Islam dan Tantangan Sekularisme Pendidikan - Ukhti Adithya Rachma; Ayyub Fadhilah; Isna Sabilil Hayati (Jurnal Pendidikan Guru Profesional, 2026)
This study examines the philosophy of Islamic education as a response to the challenges of secularism in modern educational systems, with a comparative focus on the thought of Al-Ghazali and Syed Muhammad Naquib Al-Attas. Specifically, it analyzes how the epistemological frameworks of both scholars offer concrete and systematic solutions to the secularization of education. The method employed is library research using content analysis and comparative analysis of 25 primary and secondary sources selected based on criteria of relevance, currency, and scholarly authority. The findings indicate that: (1) educational secularism causes epistemological fragmentation that separates knowledge from transcendental values, resulting in a moral and identity crisis among students; (2) Al-Ghazali emphasizes the concept of ta'lim al-qalb (education of the heart) as a counterbalance to intellectualism, while Al-Attas develops the concept of ta'dib as an epistemological alternative that rejects the dichotomy between religious and general knowledge; (3) integrating tauhid values into the curriculum and strengthening character education grounded in akhlak are strategic steps that can be practically implemented in Islamic educational institutions. The implications of this study provide a theoretical framework for curriculum developers and educators in designing holistic educational systems capable of producing generations that are not only academically intelligent but also faithful and morally upright.